Addition of Tumeric Flour in Ration on The Growth of Super-Native Chickens Aged 11-18 Weeks - Ni Ketut Etty Suwitari; Luh Suariani; Agung Pramuji; Adi Wiratama (International Journal of Scientific Multidisciplinary Research, 2023)
The main components in turmeric are essential oils and curcuminoids, which are yellow color substances in turmeric, essential oils, and Curcuminoids can increase the digestibility of dry matter and protein, increase digestive enzymes so that feed digestibility increases and results in the digestive tract emptying faster, and ultimately provide consumption increases. The design used is a completely randomized design (CRD) with 5 (five) treatments and 3 (three) replicates.  The experimental treatments are designated as follows: P0 represents the control group without the addition of turmeric flour, P1 represents the group with 1% turmeric flour, P2 represents the group with 2% turmeric flour, P3 represents the group with 3% turmeric flour, and P4 represents the group with 4% turmeric flour. This study's variables recorded and analyzed included initial body weight, final body weight, weight gain, ration consumption, and feed conversion ratio  The findings of this investigation demonstrated that The incorporation of turmeric flour showed a statistically significant effect (P <0.05) on Final Body Weight, Weight Gain, and Feed Consumption Ratio. However, it was shown that the variables under investigation did not significantly impact ration consumption (P>0.05). Giving turmeric flour up to 2% can provide the best results